Glycogen synthase kinase-3β inhibition enhances myelination in preterm newborns with intraventricular hemorrhage, but not recombinant Wnt3A - Preeti Dohare; Bokun Cheng; Ehsan Ahmed; Vivek Yadala; Pranav Singla; Sunisha Thomas; Robert Kayton; Zoltan Ungvari; Praveen Ballabh (Neurobiology of Disease, 2018)
Intraventricular hemorrhage (IVH) in preterm infants results in reduced proliferation and maturation of oligodendrocyte progenitor cells (OPCs), and survivors exhibit reduced myelination and neurological deficits. Wnt signaling regulates OPC maturation and myelination in a context dependent manner. Herein, we hypothesized that the occurrence of IVH would downregulate Wnt signaling, and that activating Wnt signaling by GSK-3β inhibition or Wnt3A recombinant human protein (rh-Wnt3A) treatment might promote maturation of OPCs, myelination of the white matter, and neurological recovery in premature rabbits with IVH. These hypotheses were tested in autopsy samples from preterm infants and in a rabbit model of IVH. Induction of IVH reduced expressions of activated β-catenin, TCF-4, and Axin2 transcription factors in preterm newborns. Both AR-A014418 (ARA) and Wnt-3A treatment activated Wnt signaling. GSK-3β inhibition by intramuscular ARA treatment accelerated maturation of OPCs, myelination, and neurological recovery in preterm rabbits with IVH compared to vehicle controls. In contrast, intracerebroventricular rh-Wnt3A treatment failed to enhance myelination and neurological function in rabbits with IVH. ARA treatment reduced microglia infiltration and IL1β expression in rabbits with IVH relative to controls, whereas Wnt3A treatment elevated TNFα, IL1β, and IL6 expression without affecting microglia density. GSK-3β inhibition downregulated, while rh-Wnt3A treatment upregulated Notch signaling; and none of the two treatments affected the Sonic-Hedgehog pathway. The administration of ARA or rh-Wnt3A did not affect gliosis. The data suggest that GSK-3β inhibition promoted myelination by suppressing inflammation and Notch signaling; and Wnt3A treatment failed to enhance myelination because of its pro-inflammatory activity and synergy with Notch signaling. GSK-3β inhibitors might improve the neurological outcome of preterm infants with IVH.